Plasma levels of immunosuppressive mediators during cardiopulmonary bypass - E. Borrelli; P. Giomarelli; A. Naldini; E. Luzzi; S. Silvestri; M. Gardinali; V. Bocci (Mediators of Inflammation)
The aim of this study was to evaluate plasma levels of two mediators with immunosuppressive properties, complement fraction C3a (C3a) and transforming growth factor-β1 (TGF-β1), during extracorporeal circulation. The proliferation index after phytohaemagglutinin (PHA) stimulation of isolated peripheral blood mononuclear cells was also investigated. Sixteen patients undergoing hypothermic (n = 8, group 1) and normothermic (n = 8, group 2) cardiopulmormry bypass (CPB) were enrolled in this study. As a control, we evaluated four patients undergoing thoracovascular operations without CPB. Blood samples were collected before CPB but after anaesthesia, every 30 min during CPB, at the end of CPB and 10 min after protamine administration. Both C3a and TGF-β1 increased significantly during CPB and after protamine administration in the hypothermic as well as the normothermic group. In the latter case the increase of C3a and TGF-β1, although more prominent, was not significantl higher than in the former group. Conversely, the proliferation, index of peripheral mononuclear cells had already decreased 30 min after CPB was started and remained depressed throughout the CPB time. These results suggest a possible role of C3a and TGF-β1 in the immunological changes occurring during extracorporeal circulation.